LUNGS IN ANTIPHOSPHOLIPID SYNDROME – THREE CASE REPORTS - Zlata Remškar (Zdravniški Vestnik, 2001)
Background. Three patients with antiphospholipid syndrome and lung involvement are presented. Except in one case, lung pathology was caused most probably by thrombotic and thrombembolic events in the lung circulation due to antiphospholipid syndrome. In one case however, equivalents of ARDS were observed with two differential diagnostic possibilities – catastrophic antiphospholipid syndrome and exacerbation of systemic vasculitis with secondary antiphospholipid activity. Conclusions. We emphasize the possibility of lung involvement in antiphospholipid syndrome due to thrombotic and thrombembolic events in lung circulation.